(untitled) (FAVE Sección Ciencias Veterinarias, 2017)
In this in vitro assay was evaluated: (i) the effect of pH on the bactericidal activity of ciprofloxacin (CFX) against a native strain of Escherichia coli, (ii) the effect of persister bacteria on the concentration-dependent mode of action of CFX. The antibacterial activity of CFX decreased with reductions of pH, so the values of minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and minimum eradication bacterial concentration (MEBC) were increased when the pH of the culture medium decreased from 7.4 to 6.5 and 5.5. The kinetics of bacterial elimination of CFX presented a biphasic pattern because of the selection of a sub-population of persistent bacteria which presented a slower elimination rate. Therefore, the antibacterial activity of CFX was determined by its concentration in reference to MIC values and the time during which the exposure of the bacteria was maintained.